2022
DOI: 10.1371/journal.pone.0273911
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber intake and metabolic syndrome in postmenopausal African American women with obesity

Abstract: Fiber intake may be associated with lower risk of metabolic syndrome (MetS) but data from metabolically unhealthy African American women is sparse. We examined the association of dietary fiber intake and MetS among postmenopausal African American women with obesity. Baseline cross-sectional data from the Focused Intervention on Exercise to Reduce CancEr (FIERCE) trial of 213 women (mean age 58.3 years) were used. Dietary intake was assessed by Food Frequency Questionnaires (FFQs). Multivariate linear and logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Increasing fiber intake reduces the risk of developing metabolic syndrome. An increase in fiber intake of 10 g per 1000 kcal reduced the risk of metabolic syndrome by 0.1 unit [ 78 ]. By increasing fiber intake, the composition of the intestinal flora changes.…”
Section: Dietary Intervention Of Chronic Diseases In Menopausementioning
confidence: 99%
“…Increasing fiber intake reduces the risk of developing metabolic syndrome. An increase in fiber intake of 10 g per 1000 kcal reduced the risk of metabolic syndrome by 0.1 unit [ 78 ]. By increasing fiber intake, the composition of the intestinal flora changes.…”
Section: Dietary Intervention Of Chronic Diseases In Menopausementioning
confidence: 99%
“…& 2014. Serat pangan memberikan pengaruh yang cukup besar terhadap zat gizi, sering dianggap sebagai makanan sehat untuk seseorang dengan risiko penyakit kardiovaskular, kolesterol tinggi, hipertensi, dapat bermanfaat bagi penderita diabetes melitus karena dapat mereduksi absorpsi glukosa usus, dapat dikaitkan dengan risiko sindrom metabolik lebih rendah (Soliman 2019;Chen et al 2016;Mao et al 2021;Lepping et al 2022).…”
Section: Kadar Serat Panganunclassified
“…A number of studies have demonstrated an inverse relationship between fiber intake and the prevalence of MetS. Lepping et al [5 ▪ ] found an inverse association between total fiber intake and MetS among postmenopausal African--American women with obesity. The researchers observed that women who consumed more fiber had better metabolic profiles, and were less likely to have MetS.…”
Section: Inverse Association Between Total Fiber Intake and Metabolic...mentioning
confidence: 99%